Pengembangan Media Scrapbook “Petualangan Luar Angkasa” Materi Tata Surya Untuk Siswa Sekolah Dasar - Yusril Alam Narutama (AL-ASASIYYA: Journal Of Basic Education, 2022)
The low level of learning of students in studying the material of the solar system. Because the learning media is less interesting so students do not understand about the solar system and celestial bodies. The lack of scrapbook learning media for students of SDN 2 Lengkonglor Nganjuk, students like learning materials with simple colors, ordinary fonts, choosing medium font sizes, students choosing original images. So that causes a lack of interest in student learning and has an impact on student learning outcomes. The purpose of this study was to determine the development procedure, validity, effectiveness, and practicality of scrapbook media on solar system materials. This research uses Research and Development (RD) research and development methods with the ADDIE Analyze, Design, Development, Implementation, and Evaluation Model. The instrument consists of a validation sheet for expert validators, teacher and student response questionnaires, evaluation questions. The conclusions of this research are (1) The process of developing scrapbook media using the ADDIE model through the analysis stage, hold planning or design, development stage, implementation stage, and evaluation stage. (2) The validity obtained an average of 86.75% with a very valid category (81%-100%) (3) The practicality of the teacher and student responses obtained an average practicality result of 92.65% with a very practical category (81 %-100). (4) The effectiveness obtained from classical mastery with a percentage of 91.6% scrapbook learning media is said to be effective if the classical mastery obtained by students is 85%.